Guest editors’ introduction to the 4th issue of Experimental Software and Toolkits (EST-4) - Mens, Kim; van den Brand, M.G.J.; Kienle, Holger M. (Science of computer programming, 2014)
Experimental software and toolkits play a crucial role in computer science. Elsevier’s Science of Computer Programming special issues on Experimental Software and Toolkits (EST) provide a means for academic tool builders to get more visibility and credit for their work, by publishing a paper along with the corresponding system in a peer-reviewed journal. Typically, tools are presented from both a user and a developer perspective, addressing tool-building issues such as architecture and design, requirements, methodologies and process aspects. This is already the fourth edition of EST with no less than 17 published systems covering application areas ranging from software analysis and visualization to teaching and software development support.